From Brothers to Neighbors and Back. - (De)Constructing Multi-Ethnic Nationalisms in Socialist Federations (KULT_online, 2016)
The collection of essays investigates the emergence and decline of different concepts of brotherhood in former socialist countries through case-studies devoted primarily to Yugoslavia and Czechoslovakia. Chosen topics cover the diverse media through which the brotherhood ideology was constructed, as well as the channels of jeopardization of these supranational projects, including theatre, art exhibitions, popular literature, film, frescoes, historiography, fashion, rock music, photographs from the front, and politicians' interaction. Due to an impressive variety of empirical approaches towards the topic and a thought-provoking theoretical framework, the collection offers indispensable historiographical material for researchers dealing with multi-ethnic societies.